ANALISIS KETERAMPILAN GURU DALAM MEMBERIKAN PENGUATAN DI RA AL-QUR’AN ULFAH PADANGSIDIMPUAN - Nurul Arafah; Wan Nova Listia (CV. Adiba Aisha Amira, 2025)
This research aims to analyze teachers’ skills in providing reinforcement, both verbal and nonverbal, at RA Al-Qur’an Ulfah Padangsidimpuan. Reinforcement is one of the eight basic teaching skills which plays an important role in increasing student’s motivation, focus and positive qualitative approach with data collection techniques through observation and documentation of two class teachers. The research result show that teachers at RA Al-Qur’an Ulfah have implemented verbal reinforcement through sentences of praise, motivation, and positive direction to students during the learning process. Meanwhile, nonverbal reinforcement is carried out through facial expressions, body movements, touch, symbols of objects of appreciation, and fun activities. The reinforcement provided is proven to be able to increase children’s enthusiasm for learning, strengthen memorization, encourage good behavior, and create a positive learning atmosphere. However, there is still a need to increase variation and consistency in providing reinforcement according to the characteristics of each child. Thus, the skill of providing appropriate and effective reinforcement is very important in supporting a meaningful and enjoyable learning process in early childhood education institutions.